The State of the Art of Thermo-Chemical Heat Storage - Vasta, Salvatore (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The heat storage based on thermochemical technology is associated with higher amounts of energy stored with respect to systems based on sensible heat. This interesting feature is stimulating the interest of the scientific community, among energy providers and grid managers, since it can effectively support the operation and integration of renewable high-efficiency systems and local smart grids. Research in this field is achieving unprecedented goals thanks to the profitable exploitation of results obtained in the field of heat pumps and thermally driven systems. The present issue offers the reader a sensational window to this rapidly evolving world.